DEVELOPMENT OF FARMS IN UKRAINE: WARTIME CHALLENGES AND LAND MANAGEMENT ASPECTS - Тітова, Світлана; Белицький, Андрій (SWorldJournal, 2025)
The article examines the current state of farms in Ukraine in wartime, their role in ensuring the stability of the agricultural sector and prospects for development. A graphical model has been developed that reflects the advantages of farms compared to la